Pengaruh Modal Sendiri dan Lokasi Usaha Terhadap Pendapatan Usaha Mikro Kecil Menengah (UMKM) di Kabupaten Tabanan (Modal Pinjaman sebagai Variabel Intervening) - Putri, Ni Made Dwi Maharani; Jember, I Made (Jurnal Ekonomi Kuantitatif Terapan; 2016: Vol. 9, No. 2, Agustus 2016 (pp. 89 - 176)DO - 10.24843/JEKT.2017.v09.i02.p07)
Micro, Small and Medium Enterprises (SMEs) are the most important part in the economy. Many government efforts to assist the development of SMEs by providing a forum for businesses in the form of credit / loan capital is expected to encourage businesses to increase revenue. The purpose of this study was to determine the influence of their own capital, business location and loan capital directly and the indirect effect between equity and income through the business premises against the loan capital. This research was conducted in all districts in Tabanan. Research carried out by conducting a survey with a questionnaire. The data used in this study are primary data, while the analysis method used is the analysis of lane or path analysis to determine the effect, directly and Sobel test to determine the effect indirectly. The analysis showed the capital itself has a positive influence on capital loans and business location has a positive influence on the loan capital. Business location and loan capital has a positive effect on income. The coefficient of determination total at about 85 percent is explained by the model and the remaining 15 percent is explained by other variables outside the model.
Keywords: Modal Sendiri, Lokasi Usaha, Modal Pinjaman, Pendapatan